The impact of sectoral minimum wage laws on employment, wages, and hours of work in South Africa - Haroon Bhorat; Ravi Kanbur; Natasha Mayet (IZA Journal of Labor & Development, 2013)
This paper attempts to investigate the impact of sectoral wage laws in South Africa. Specifically, we examine the impact of minimum wage laws promulgated in the Retail, Domestic work, Forestry, Security, and Taxi sectors using 15 waves of biannual Labour Force Survey data for the 2000-2007 period. Using a quasi-experimental approach, we apply two alternative specifications of a difference-in-differences model to estimate the impact of multiple minimum wage laws in South Africa on employment, wages, and hours of work. In order to assess whether the changes experienced by workers in the sectors analysed were unique to those sectors, a unique control group is identified for each sector. We find some evidence of a significant increase in real hourly wages in the post-law period in four of the five sectors examined. Our results also suggest that whilst there was no significant impact of the laws at the extensive margin, there was some evidence of an adjustment at the intensive margin in certain sectors. We also find that in three of the five sectors, increases in real hourly wages were sufficient to outweigh intensive margin adjustments so that workers in these sectors experienced an improvement in real monthly income as a result of the law.
Keywords: C21; J23; J30; J31; J38; 330; Minimum wage; South Africa; Wage; Employment; Hours of work; Mindestlohn; Beschäftigungseffekt; Lohnniveau; Arbeitszeit; Einzelhandel; Sicherheitsgewerbe; Landwirtschaft; Taxigewerbe; Südafrika